PEMETAAN SPASIAL KEJADIAN COVID-19 BERDASARKAN FAKTOR PEJAMU DI KABUPATEN MINAHASA SELATAN - Christian Tambingon; Grace Debbie Kandou; Barnabas Harold Ralph Kairupan (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Background: COVID-19 is an infectious disease that has become a global problem. North Sulawesi Province in 2020 has 6 Regencies/Cities declared as local transmission areas, including South Minahasa Regency. The number of COVID-19 cases in South Minahasa Regency as of November 12 2020 was ranked 6th out of 16 Regencies/Cities in North Sulawesi. The purpose of this study was to find out the spatial distribution and host factors for the incidence of COVID-19 in South Minahasa Regency. Methods: Descriptive observational research was conducted using a Geographic Information System (GIS) approach in 421 cases in South Minahasa District. The variables in this study were the incidence of COVID-19 in South Minahasa Regency based on gender, age, symptom onset date, confirmed date, history of close contact, and comorbid diseases (hypertension and diabetes mellitus). Data were analyzed using Quantum GIS in mapping and displaying spatial information. The results of spatial data processing are presented in the form of an image map of the area based on variables. Results: The incidence of COVID-19 in South Minahasa Regency was found more in female respondents and the age group above 54 years. December 2020 was the highest time of onset and confirmed cases of COVID-19. Most of the respondents did not have comorbid hypertension and DM. Conclusion: There needs to be education about community behavior in preventing the transmission of COVID-19, namely using masks when doing activities outside the home, maintaining social distancing, washing hands with soap and running water, and completing the status of COVID-19 vaccinations to advanced vaccine doses ( booster) in South Minahasa Regency.